Slow adjustment to shocks or true hysteresis? Lessons from the different labour market performances in Western Europe and the USA - Wim Kösters; Ansgar Belke (Intereconomics, 1996)
In Western Europe in the last two decades the unemployment rate has increased during cyclical downturns only to persist at or around the higher level in the following phase of economic recovery. One of the most notable exceptions to this pattern of unemployment persistence, often termed hysteresis, is the United States. The following article examines the empirical evidence and the possible theoretical explanations for this difference.
Keywords: 330; Unemployment